Female patients with coronary artery disease and aortic stenosis undergoing a surgical or interventional treatment in terms of revascularization and valve replacement. (3rd October 2022) - Fortmeier, V; Hoeflsauer, K; Mueller, P; Potratz, M; Friedrichs, K P; Scholtz, S; Gummert, J; Rudolph, V; Gilis-Januszewski, T; Bleiziffer, S; Rudolph, T
Abstract: Background: Coronary artery disease (CAD) in female patients undergoing a Transcatheter Aortic Valve Implantation (TAVI) is accompanied with a worse outcome compared to those without CAD. Nevertheless, it is still unclear whether a complete revascularization and outcome are achieved similarly in women treated with an interventional (PCI plus TAVI) or surgical (CABG plus SAVR) treatment strategy. Purpose: This study aims to compare the completeness of revascularization in terms of residual SyntaxScore and to evaluate the differences in 30-days (short-term), one-year and three-years (intermediate term) mortality in women with CAD and AS undergoing a surgical or catheter-based treatment. Methods: Patients were recruited at one tertiary center in Germany between 2016 and 2019. Initially the surgical group contained 932 patients and the interventional cohort 360 patients as a result of setting a maximum time interval of 3 months between PCI and TAVI. The surgical group (CABG+SAVR) and the interventional group (PCI+TAVI) were compared by using a propensity score analysis. Age, left ventricular function, EuroSCORE II and degree of CAD served as matching parameters so that the matched female cohort finally consisted of 114 patients (57 patients treated interventionally, 57 treated surgically). Syntax Score was measured before and after revascularization. As a primary endpoint all-cause mortality was analyzed at 30 days, one and three years after the procedure. Results: Median age was 80 years both in the interventional and surgical cohort (p=0.298). Both groups represented a moderate to high-risk population (EuroScore II in PCI+TAVI: 4.39 [2.83–8.82] vs 6.18 [3.43–8.6] in CABG+SAVR (p=0.279) and showed no significant difference in median pre-interventional/preoperative SyntaxScore I (PCI+TAVI: 16.00 [9–26.5] vs CABG+SAVR: 18 [9.5–25.5]; p=0.719). In the interventional group coronary physiology was measured more frequently (6.8% vs 1.8%, p=0.024). There was no significant difference in the presence of an aortoostial lesion, heavy calcification and a length of the lesion >20mm between PCI+TAVI and CABG+SAVR before therapy (PCI+TAVI vs CABG+SAVR: 11.1% vs 13.0%, p=0.581; 60.5% vs 55.1%, p=0.289; 20.4% vs 25.1%, p=0.316). The main stem as target lesion was present in both groups with no significant difference (PCI+TAVI vs CABG+SAVR: 8.8% vs 19.3%, p=0.106). Median residual SyntaxScore I was significantly higher in PCI+TAVI than in CABG+SAVR (5.0 [0.0–13.0] vs 0.0 [0.0–8.5], p=0.03). No significant difference in 30-days, 1-year and 3-years mortality was observed between the interventional and surgical group (PCI+TAVI vs CABG+SAVR: 3.5% vs 8.8%, p=0.242; 10.5% vs 14%, p=0.568; 22.8% vs 15.8%, p=0.342). Conclusion: Female patients with AS and CAD with low SyntaxScore undergoing CABG+SAVR reach a more complete revascularization than those treated interventionally. Nevertheless, this fact seems to have no influence on short and intermediate term mortality. Funding Acknowledgement: Type of funding sources: None.